2007
DOI: 10.1518/001872007x215674
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Emergency Awakening to Audible Smoke Alarms: An Update

Abstract: Objective: This review examines research on arousal from sleep in an emergency. It considers whether the current smoke alarm signal is optimal for waking those most at risk of dying in a fire and, if not, how it may be improved. Background: The fire fatality rate during the sleeping period is approximately three times greater than at other times. Method: Four key areas are reviewed: (a) the characteristics of four signals (high-frequency beeping, Temporal 3, voice, and naturalistic sounds); (b) how human chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Research has shown that musical stimuli with melodic features (instrumental, Vivaldi’s Four Seasons ‘Spring’ concerto) increases task performance when compared to silent conditions (41, 44), and it is posited by Riby (44) that this may be a consequence of music’s ability to increase arousal and enhance cognition. Additionally, the mode in which the music is sounded has been attributed to improvements in performance (45), and that pitches in the range of the female human voice (~ < 2500 Hz) may be more successful in arousing sleeping humans than male (90). The frequency range of the melodic treatment in this study resides between 1318.5 Hz and 2637 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that musical stimuli with melodic features (instrumental, Vivaldi’s Four Seasons ‘Spring’ concerto) increases task performance when compared to silent conditions (41, 44), and it is posited by Riby (44) that this may be a consequence of music’s ability to increase arousal and enhance cognition. Additionally, the mode in which the music is sounded has been attributed to improvements in performance (45), and that pitches in the range of the female human voice (~ < 2500 Hz) may be more successful in arousing sleeping humans than male (90). The frequency range of the melodic treatment in this study resides between 1318.5 Hz and 2637 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…The perceived increase occurs because the different frequencies activate different parts of the basilar membrane [34]. In addition, the multiple frequency peaks are less likely to be masked by ambient noise than a single frequency sound and lower frequencies penetrate walls and doors better than higher frequencies [28].…”
Section: Discussionmentioning
confidence: 99%
“…It was first specified by ISO in 1987 [26] and was first adopted in Canada in 1995, the USA in 1996 [27] and Australia in 2004 [28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One recent study reports that women with persistent depressive symptoms were approximately 3.6 times more likely (95% CI ¼ 0.11-0.7) to not have a working smoke alarm (Chung, McCollum, Elo, Lee, & Culhane, 2004). However, one challenge to bringing the benefits of smoke alarms to potentially vulnerable populations is that hypnotics and alcohol have been shown to impair adults' ability to hear smoke alarms while sleeping (Bruck & Ball, 2007). Alarms that emit lower frequency signals appear to be more effective under conditions of alcohol impairment.…”
Section: Preventionmentioning
confidence: 99%